No Relationship between Maternal Iron Status and Postpartum Depression in Two Samples in China - Rinat Armony-Sivan; Jie Shao; Ming Li; Gengli Zhao; Zhengyan Zhao; Guobing Xu; Min Zhou; Jianying Zhan; Yang Bian; Chai Ji; Xing Li; Yaping Jiang; et al. (Journal of Pregnancy)
Maternal iron status is thought to be related to postpartum depressive symptoms. The purpose of the present study was to evaluate the relationship between pre- and postnatal maternal iron status and depressive symptoms in pilot (n=137) and confirmatory (n=567) samples of Chinese women. Iron status was evaluated at mid- and late pregnancy and 3 days postpartum. The Edinburgh Postnatal Depression Scale (EPDS) was used to assess maternal postpartum depression 24–48 hours after delivery and 6 weeks later. In the pilot sample, correlations between early- and late-pregnancy maternal Hb and EPDS scores at 6 weeks were r=0.07 and −0.01, respectively (nonsignificant). In the confirmatory sample, the correlations between maternal iron measures (Hb, MCV, ZPP, ferritin, sTfR, and sTfR Index) in mid- or late pregnancy or 3 days postpartum and EPDS scores shortly after delivery or at 6 weeks were also low (r values < 0.10). EPDS scores in anemic and nonanemic mothers did not differ, regardless of sample or timing of maternal iron status assessment. In addition, women with or without possible PPD were similar in iron status in both samples. Thus, there was no relationship between maternal iron status and postpartum depression in these samples.